2015
DOI: 10.3897/zookeys.500.8725
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of the Liolaemus elongatus-kriegi complex (Iguania, Liolaemidae) from Andean highlands of southern Chile

Abstract: The elongatus-kriegi complex is one of the most diverse clades of the Liolaemus (sensu stricto) subgenus of lizards. There are currently 29 species recognized in this group distributed between Chile and Argentina. Based on molecular evidence, there seem to be five main clades nested within this complex: the elongatus, leopardinus, kriegi, petrophilus and punmahuida clades. Liolaemus buergeri and Liolaemus kriegi, both of the kriegi clade, were believed to inhabit the surroundings of the Laja Lagoon, in the Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 27 publications
(81 reference statements)
1
21
0
3
Order By: Relevance
“…However, DNA data from all these have not been shared in GenBank or other online databases (Avila et al 2010, 2012, 2015, Escobar-Huerta et al 2015, Esquerré et al 2014, Martínez et al 2011) which does not allow the replication of the provided phylogenies or genetic distances. Two described species (Quinteros 2012, Troncoso-Palacios et al 2015a), Liolaemus abdalai and Liolaemus zabalai , are supported in regards to DNA features by previously published phylogenetic works. Nine species ( Liolaemus aparicioi , Liolaemus carlosgarini , Liolaemus choique , Liolaemus chungara , Liolaemus nigrocoeruleus , Liolaemus pyriphlogos , Liolaemus riodamas , Liolaemus scorialis and Liolaemus smaug ) have been described without the support of molecular data (Abdala et al 2010, Esquerré et al 2013, Marambio-Alfaro and Troncoso-Palacios 2014, Ocampo et al 2012, Quinteros 2012, Quinteros et al 2014, Troncoso-Palacios et al 2015a).…”
Section: Discussionsupporting
confidence: 71%
“…However, DNA data from all these have not been shared in GenBank or other online databases (Avila et al 2010, 2012, 2015, Escobar-Huerta et al 2015, Esquerré et al 2014, Martínez et al 2011) which does not allow the replication of the provided phylogenies or genetic distances. Two described species (Quinteros 2012, Troncoso-Palacios et al 2015a), Liolaemus abdalai and Liolaemus zabalai , are supported in regards to DNA features by previously published phylogenetic works. Nine species ( Liolaemus aparicioi , Liolaemus carlosgarini , Liolaemus choique , Liolaemus chungara , Liolaemus nigrocoeruleus , Liolaemus pyriphlogos , Liolaemus riodamas , Liolaemus scorialis and Liolaemus smaug ) have been described without the support of molecular data (Abdala et al 2010, Esquerré et al 2013, Marambio-Alfaro and Troncoso-Palacios 2014, Ocampo et al 2012, Quinteros 2012, Quinteros et al 2014, Troncoso-Palacios et al 2015a).…”
Section: Discussionsupporting
confidence: 71%
“…This species is characterized by 1) small size (maximum snout vent length = 69.6 mm), 2) lack of dorsal pattern, 3) high number of midbody scales (82–98), 4) precloacal pores present in males, and 5) absence of dark rings on the tail. We provide a differential diagnosis with regards to all species currently considered to be members of this clade, plus Liolaemus scorialis Troncoso-Palacios Díaz, Esquerré & Urra, 2015, the assignment of which is under study, but probably is related to the Liolaemus elongatus clade (Troncoso-Palacios et al 2015). Table 1 summarizes some of the diagnostic traits.…”
Section: Resultsmentioning
confidence: 99%
“…Recent expeditions to seldom explored highlands and the revision of the taxonomic status of some populations has led to the description of several new species (Escobar-Huerta et al 2015, Esquerré et al 2013, 2014, Núñez 2007, Troncoso-Palacios et al 2015). In fact, it has been thought that Chilean species of the Liolaemus elongatus-kriegi complex have a small distribution in central Chile (Morando et al 2003), but currently it is known that this group of lizards is widely distributed in central and southern Chile, and it is also probable that some populations under study could be described as new species in the future (Troncoso-Palacios unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of dorsal scales in L. buergeri is quite variable -in the sample of Troncoso-Palacios et al (2015b) it varied between 78 and 91 but Medina, Avila & Morando (2013) found values higher than 100. The number of ventral scales is between 111 and 125 (Troncoso-Palacios et al, 2015b). Liolaemus flavipiceus has 60-71 dorsal and 93-105 ventral scales (Troncoso-Palacios et al, 2015b).…”
Section: Present Name Liolaemus Conspersusmentioning
confidence: 99%